2014
DOI: 10.1002/ente.201402039
|View full text |Cite
|
Sign up to set email alerts
|

Water Loss Versus Soaking Time: Spontaneous Imbibition in Tight Rocks

Abstract: The combined application of multilateral horizontal drilling and multistage hydraulic fracturing has successfully unlocked unconventional tight hydrocarbon reservoirs. However, the field data show that only a small fraction of the injected water during hydraulic fracturing treatments is recovered during flowback operations. The fate of nonrecovered water and its impact on hydrocarbon production are poorly understood. This paper aims at understanding the relationship between water loss and rock petrophysical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…The wettability of shale reservoir rocks has been experimentally investigated by a number of researchers for shale rocks across the US (Odusina et al 2011;Wang et al 2012), Canada (Borysenko et al 2009;Makhanov 2013;Xu and Dehghanpour 2014;Lan et al 2014;Lan et al 2015), Australia , China (Liang et al 2016) and Poland (Ksiezniak et al 2015). Lan et al (2014;2015) studied the effect of wettability on the imbibition dynamics by comparing the behaviors of water and oil phases on rock samples from two shale plays in Western Canada, the Montney and Horn River. They observed that the oil completely spreads on the shale sample, while water droplets show a measurable contact angle that is greater than 37 o , therefore, they concluded that the observed wettability cannot be fully explained by the contact angle results.…”
Section: Wettabilitymentioning
confidence: 99%
“…The wettability of shale reservoir rocks has been experimentally investigated by a number of researchers for shale rocks across the US (Odusina et al 2011;Wang et al 2012), Canada (Borysenko et al 2009;Makhanov 2013;Xu and Dehghanpour 2014;Lan et al 2014;Lan et al 2015), Australia , China (Liang et al 2016) and Poland (Ksiezniak et al 2015). Lan et al (2014;2015) studied the effect of wettability on the imbibition dynamics by comparing the behaviors of water and oil phases on rock samples from two shale plays in Western Canada, the Montney and Horn River. They observed that the oil completely spreads on the shale sample, while water droplets show a measurable contact angle that is greater than 37 o , therefore, they concluded that the observed wettability cannot be fully explained by the contact angle results.…”
Section: Wettabilitymentioning
confidence: 99%
“…Experimental work can build on this knowledge to help understand the interactions between these different structural domains, in order to build an appropriate effective medium description of shale. In addition, multiphase flow in shales is an important area of study to understand fluid migration, and shed light on the fate of unrecovered fracturing fluids from stimulation operations and their effect on productivity (Lan et al 2014, Ghanbari andDehganpour 2015). Spontaneous fracturing fluid (mostly water) uptake by shales can be attributed to capillary forces, adsorption, or osmosis (Zhou et al 2016, Ghanbari andDehganpour 2015).…”
Section: Introductionmentioning
confidence: 99%
“…What’s more, capillary trapping, near fracture water-block and relative permeability reduction can also be the potential killer for oil and gas production 1618 . At the same time, scholars also find that hydrocarbon production in Marcellus has significantly improved after undergo 6 months’ shut-ins after hydraulic fracturing 19 . Scholars always explain this phenomenon by near fracture water-block removal or aqueous phase redistribution due to capillary dominated spontaneous imbibition.…”
Section: Introductionmentioning
confidence: 93%